Implemantiation Of Video Tutorials In Art Center Activities As An Effort To Stimulate Fine Motor Skilis In Early Childhood - Dwi Nomi Pura; Yuliza Andriyani Siregar; Melia Distri Yeni (Utan Kayu Publishing, 2025)
This study aims to implement and analyze the effectiveness of art activity video tutorials in the Art Center as a medium for stimulating fine motor skills in early childhood. Using a classroom action research (CAR) method with participants from Group B children (aged 5–6 years) in a kindergarten, instructional videos were developed containing demonstrations of activities such as tearing and pasting, cutting patterns, and paper folding. The results indicate that the implementation of video tutorials significantly improved children's fine motor skills, as evidenced by enhanced hand-eye coordination, finger movement accuracy, and hand muscle strength. The presence of video tutorials functioned as an engaging and clear visual model that successfully focused children's attention, increased learning motivation, and guided them to perform art activities more independently. The implications of this study suggest that video tutorials can be adopted as an innovative and effective medium to optimize the function of the Art Center in supporting fine motor development in early childhood education.